Socio-Economic Educational Interest of the Children in India: Exploring the Legislative Protection of Minors' Socio-Economic and Educational Interests in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India, the national government as well as a number of the individual state governments hascome up with a variety of programmes in order to get children who are not currently enrolled in schoolback into the educational system. The researcher comes to the conclusion that minors' economic andeducational interests and rights are protected by legislative laws after examining the position under theGuardian and Wards Act 1890, the Hindu Minority and Guardianship Act 1956, the Prohibition of ChildMarriage Act 2006, and the Position of Non-residential Indians in terms of the economic and educationalprotection of children's rights. These laws were examined in terms of the protection of children's rightswith regard to marriage.